Building community resilience: can everyone enjoy a good life?. Issue 10 (2nd October 2016) - Cinderby, Steve; Haq, Gary; Cambridge, Howard; Lock, Kate
ABSTRACT: Initiatives to reduce community carbon emissions and foster sustainable lifestyles have had varying degrees of success. There is now a need for a re-energised, concerted and joined-up approach that places environmental issues in a wider context – one that improves quality of life while building community resilience. This involves enhancing the capacity of neighbourhoods to recover, respond and adapt to environmental and socio-economic changes. This paper examines the experience gained in a participatory action research (PAR) study to build community resilience, where facilitators supported residents to take ownership of their own agendas. The New Earswick Good Life Initiative (GLI) was an 18-month project undertaken in a low-income suburb of York (UK). A range of approaches were used to identify activities which had the most potential to nurture resilience and foster a shift towards greater environmental sustainability. The GLI highlighted how the introduction of new ideas not only need to be locally relevant but also requires care and time in order for them to embed within community. Altering the way a community manages its environment involves transforming social relationships, strengthening institutions and influencing local power balances. Furthermore, it is necessary to build social capital, knowledge, leadership skills and support social networks to allow communities to effectively engage with relevant local and national policies. Only by providing opportunities to develop these resilient attributes can increased local responsibility be successful. The paper concludes by providing guidance on strengthening community resilience and delivering pro-environmental behaviour change.